Elucidation of the role of lithium iodide as an additive for the liquid‐based synthesis of Li7P2S8I solid electrolyte. (10th August 2020) - Bintang, His Muhammad; Lee, Seongsoo; Kim, Jun Tae; Jung, Hun‐Gi; Chung, Kyung Yoon; Whang, Dongmok; Lim, Hee‐Dae
Summary: Liquid‐phase synthesis for a sulfide‐based solid electrolyte has been widely studied due to its great advantage of being a simpler and more cost‐effective method compared with the conventional solid‐phase synthesis, even it could induce homogeneous reactions in the solution. However, the physically and chemically stable phosphorus pentasulfide (P2 S5 ) is barely soluble in various solvents; this has been a major problem for achieving a pure solution‐phase dissolving solid electrolyte. Therefore, exploring an effective additive for liquid‐phase synthesis would be worthwhile and could potentially lead to the discovery of new chemicals to produce qualified solid electrolytes. In this paper, lithium iodide's (LiI) dual role as a strong nucleophile as well as a major reactant source for producing Li7 P2 S8 I is first investigated. The nucleophilic additive of LiI has been proven to break the P‐S bonds of P2 S5, driving the insoluble P2 S5 to become the soluble intermediate complex. Also, it is demonstrated that controlling the reaction times between the LiI and the P2 S5 is key to achieving solution‐based synthesis, and the role of LiI is investigated by conducting bonding analysis. Abstract : We elucidate the role of LiI as an additive for the liquid‐based synthesis of Li7 P2 S8 I solid electrolyte. LiI mixed with P2 S5 and 3Li2 S at the same time forms the amorphous LiI·P2 S5 ·3Li2 S; however, once LiI forms LiI·P2 S5 complex, the subsequent reaction with 3Li2 S is hard to trigger. By conducting bonding analysis, the effect of LiI as an additive and the reaction mechanism are carefully elucidated.